The Impact of Macroeconomic Variables on Overall and Segmented Stock Market Returns in China - HU, YING (2020)
In this study, three models will be constructed to explore the relationship between stock returns and macroeconomic variables in the CSI 300 overall stock market, the computer industry, and the pharmaceutical industry using ordinary least squares-multiple regression models over a 247-month period from January 2000 to June 2020. Among the seven macroeconomic variables used is the lagged change in stock returns, the lagged change in the exchange rate, the lagged change in the inflation rate, the lagged change in the price of crude oil, the lagged change in the index of industrial production, the lagged change in the import rate, and the lagged change in the growth rate of the money supply.